Microsoft Office 97 resource kit (Microsoft P. RichmondUS, 1997)
Explains how to use Microsoft (MSFT) Office 97 resource kit. Deals with new features and benefits of Office 97 namely: improved software administration; intelligent applications; and intranet and workgroup solutions. Deals in detail with: deploying MSFT Office; upgrading to MSFT Office; switching from other applications; using MSFT Office throughout an organization; and MSFT Office architecture.
Title discarded 2013-10-15. S. Barker